A five-year retrospective study of cervical fibroids in a tertiary care centre - N., Sunanda; R., Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical leiomyomas or fibroids are rare benign pelvic tumors. The symptoms vary from urinary retention, frequency, dyspareunia, intermenstrual bleeding, rarely mimicking procidentia or can cause uterine inversion. This study was conducted in a tertiary hospital to find out clinical presentation, prevalence of cervical fibroids. Methods: This study is a retrospective study where Women ranging from 20 to >60 years age attending gynecology OPD of Cheluvamba hospital tertiary care centre attached Mysuru medical college and research centre, Mysuru for abdominopelvic mass, pain, menstrual abnormalities over a period of 5 years (January 2012 to December 2016) were included the study. Socio-demographic profile, detailed menstrual history, reason for attending hospital and previous treatment taken prior to the hospital visit were recorded. Pregnant women with fibroids were excluded from the study. Parameters like type and size of cervical fibroid, mode of treatment, postoperative morbidities, histopathological reports were studied and interpreted in this study. Results: In this study total 20 women who presented with menorrhagia or with abdominopelvic mass had cervical fibroid. Of 20 patients 10 (50%) belonged to age group 31-40 years, 9 (45%) patients were of 41-50years age and 1 (5%) patient was >60 years age. The 16 (80%) patients presented with menorrhagia. Metrorrhagia was the commonest menstrual pattern seen in 15 (75%) women. Asymptomatic fibroids with abdominopelvic mass were seen in 4 (20%) women. The size was 12-28 weeks. Polypectomy was done in 1 (5%) woman and abdominal hysterectomy was done in 19 (95%) women. None of the patient had postoperative morbidity or mortality. histopathological reports in 17(85%) showed leiomyoma without degeneration while 3 (15%) cases showed degenerative changes. Conclusions: Further research is needed to find out biological factors causing fibroids including diet, stress, environmental and racial influences. Routine screening, early detection, increase awareness by early reporting to the hospital will reduces morbidity and improves quality of life socioeconomically.